Development of an Electrowetting-on-Dielectric Cellulose-Based Conductive Sensor Using Direct Inkjet Printed Silver Nanoparticles - Oriol Caro-Pérez; Maria Blanca Roncero; Jasmina Casals-Terré (Polysaccharides)
In the quest for sustainable and efficient solutions for modern electronics, flexible electronic devices have garnered global attention due to their potential to revolutionize various technological applications. The manufacturing of these devices poses significant challenges, particularly regarding environmental sustainability and ease of production. A novel method employing direct inkjet printing of silver nanoparticle (npAg) ink onto cellulose nanocrystal (CNC) substrates is presented, offering a promising alternative to conventional methods. This study demonstrates the ability of CNCs to serve as a flexible and biodegradable substrate that does not require complex post-printing treatments to achieve adequate electrical performance. This method was implemented in the fabrication of an electrowetting-on-dielectric (EWOD) device, achieving circuit patterns with high resolutions and reduced resistances. The findings not only validate the use of CNCs in flexible electronic applications but also underscore the potential of advanced printing techniques to develop flexible electronics that are environmentally sustainable and technically feasible.